Pengaruh Strategi Dakwah Sunan Bonang Terhadap Pembentukan Identitas Islam Nusantara: Tinjauan Historis - Alfadhilah, Jauharotina; Kumala, Akhla Shofia (ASWALALITA: Journal of Da'wah Management, 2025)
Islam is one of the religions practiced in Indonesia. However, due to cultural, ethnic, and religious diversity, Islam in Indonesia has developed with characteristics distinct from those of the Middle East, giving rise to the identity of Islam Nusantara. However, this does not mean a new teaching has been born; rather, Islam in Indonesia has evolved into a culture imbued with Islamic nuances, making it easily accepted by society. This process is inseparable from the efforts of the preachers who devised this powerful strategy, one of whom was Sunan Bonang. Therefore, the researcher wants to determine the extent to which Sunan Bonang's strategy influenced the formation of Islam Nusantara. The purpose of this study is to analyze Sunan Bonang's preaching approach and its impact on the acceptance of Islam among local communities, as well as his contribution to shaping the face of Islam Nusantara. This research uses qualitative methods with a hermeneutic theory approach. This approach was chosen to facilitate researchers' in-depth understanding of Sunan Bonang's missionary efforts to spread Islam on the island of Java. This study focuses on social conditions, missionary strategies, challenges, methods, and successes in spreading Islam on the island of Java, through reference to books, journals, and recent articles. The results show that Sunan Bonang utilized local arts and culture, such as gamelan, tembang (traditional Javanese music), and suluk (traditional Islamic chanting) as a means of propagating Islam. This strategy was not only effective in conveying Islamic values ​​but also created harmony between Islamic teachings and local culture, ultimately giving rise to a distinctive Nusantara Islamic identity. This research confirms that a cultural approach to missionary work plays a crucial role in creating a contextual and sustainable form of Islam in a multicultural society like Indonesia.